From SARS to SARS-CoV-2, insights on structure, pathogenicity and immunity aspects of pandemic human coronaviruses (2020)
Human Coronaviruses (HCoV), periodically emerging across the world, are potential threat to humans such as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) – diseases termed as COVID-19. Current SARS-CoV-2 outbreak have fueled ongoing efforts to exploit various viral target proteins for therapy, but strategies aimed at blocking the viral proteins as in drug and vaccine development have largely failed. In fact, evidence has now shown that coronaviruses undergoes repaid recombination to generate new strains of altered virulence; additionally, escaped the host antiviral defense system and target humoral immune system which further results in severe deterioration of the body such as by cytokine storm. This demands the understanding of phenotypic and genotypic classification, and pathogenesis of SARS-CoV-2 for the production of potential therapy. In lack of clear clinical evidences for the pathogenesis of COVID-19, comparative analysis of previous pandemic HCoVs associated immunological responses can provide insights into COVID-19 pathogenesis. In this Review, we summarize the possible origin and transmission mode of CoVs and the current understanding on the viral genome integrity of known pandemic virus against SARS-CoV-2. We also consider the host immune response and viral evasion based on available clinical evidences which would be helpful to remodel COVID-19 pathogenesis; and hence, development of therapeutic against broad spectrum of coronaviruses.